Patterns of use of long‐acting bronchodilators in patients with COPD: A nationwide follow‐up study of new users in New Zealand. Issue 6 (18th December 2017) - Parkin, Lianne; Barson, David; Zeng, Jiaxu; Horsburgh, Simon; Sharples, Katrina; Dummer, Jack
ABSTRACT: Background and objective: While several studies have found that prescribing practices do not conform to chronic obstructive pulmonary disease (COPD) treatment guidelines, none have examined longitudinal patterns of use of long‐acting beta2 ‐agonist (LABA) and long‐acting muscarinic antagonist (LAMA) therapy across an entire country. We undertook a nationwide follow‐up study to describe treatment patterns in new users of long‐acting bronchodilators. Methods: National health and pharmaceutical dispensing data were used to identify patients aged ≥45 years who initiated LABA and/or LAMA therapy for COPD between 1 February 2006 and 31 December 2013. Dispensings of LABAs, LAMAs and inhaled corticosteroids (ICSs) were aggregated into episodes of use of therapeutic regimens. Kaplan–Meier curves, sunburst plots and sequence index plots were generated to summarize, respectively, the duration of the first regimen, the sequences in which unique regimens were used and the patterns of use and non‐use during follow‐up. Results: The study cohort included 83 435 patients with 290 400 person‐years of follow‐up. The most commonly initiated regimen was a LABA with an ICS. ICS use was inconsistent with international guidelines: over‐ and under‐treatment occurred in patients with infrequent and frequent exacerbations, respectively, and ICS monotherapy was common. The median duration of the first regimen was 46 days. Many patients used multiple regimens over time and periods of non‐use were common. Conclusion: In this nationwide study, patterns of use of LABAs, LAMAs and ICSs were complex and often did not comply with treatment guidelines. Further work is required to address the discrepancy between guidelines and prescribing practices. Abstract : In this nationwide follow‐up study of patients initiating long‐acting beta2 ‐agonist (LABA) and/or longacting muscarinic antagonist therapy (LAMA) for chronic obstructive pulmonary disease, the most common first regimen was a LABA with an inhaled corticosteroid (ICS). ICS use was inconsistent with guidelines. There were complex therapy patterns, including periods of non‐use. Watch the video abstract